Pathohistological changes in the intestine, lungs and liver of sheep with spontaneous strongyloidiasis - Sorokova, S.; Yevstafieva, V.; Shchebentovska, O.; Barabolia, O.; Suprunenko, K. (Regulatory Mechanisms in Biosystems, 2021)
Sheep diseases of invasive and non-invasive etiology are among the restrictive factors for Ukrainian sheep-breeding. The helminthiases are among the most widespread parasitical diseases, and particularly strongyloidiasis causes significant losses for sheep farms in cases of severe course. Young sheep are the most susceptible, showing growth and developmental lag, and death occurs in cases of high invasiveness due to severe pathologies induced by the parasites. Thus the aim of the present work was to study the morphological and histological changes in the intestine, lungs and liver of sheep with strongyloidiasis. Results of pathoanatomy showed that under spontaneous sheep strongyloidiasis with the intensity of the invasion from 50 to 136 specimens of nematodes, the main pathological changes occur at Strongyloides localization sites: intestine and parenchymatous organs (lungs and liver). Particularly, the small intestine showed catarrhal desquamative enteritis. Morphological changes of its mucosa demonstrated necrosis of the apical part of the villi, desquamation of epithelium, constriction and decrease of intestinal crypts. At the same time, massive diffusive cell infiltrates were detected in the intestinal mucosa lamina propria with the prevalence of eosinophilic leukocytes, inflammatory thickening of villi cylindrical epithelium and its mucous metamorphosis, pyknosis and lysis of enterocyte nuclei. In the large intestine, necrosis of the mucosa was detected, with edema, effusion of serum-cell exudate in its canal, diffusive infiltration of lymphocytes, eosinophils and plasma cells in the intestinal mucosa lamina propria. Lung tissue demonstrated parasite larvae localized in canals of the bronchi and in alveoli. These sites had diffusive hemorrhages in lung parenchyma, signs of inflammation and thickening of interstitial tissue caused by damage to vessel walls due to migration of parasite larvae. Histological changes in the liver of sheep with strongyloidiasis showed the development of granular dystrophy and necrotic changes in hepatocytes.